2020
DOI: 10.15244/pjoes/109027
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Synthetic Organic Reactive Dye Wastewater Using GO-TiO<sub>2</sub> Nanocomposite

Abstract: Most of the organic dyes used in textile industries are highly carcinogenic. 25-35% of these dyes get consumed during the textile dyeing process and the remaining portion of the dye is directly discharged into different environmental components as aqueous effluent. It is widely known that some azo dyes and degradation products such as benzidine, naphthalene, etc., released from textile industries cause severe health and environmental hazards [1].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…While the absorption peak of GO‐TiO 2 materials at 546 and 683 cm −1 corresponds to the stretching vibration peak of Ti─O bond. Combined with the XRD patterns of GO‐TiO 2 , find GO‐TiO 2 materials were successfully prepared 25,26 …”
Section: Resultsmentioning
confidence: 99%
“…While the absorption peak of GO‐TiO 2 materials at 546 and 683 cm −1 corresponds to the stretching vibration peak of Ti─O bond. Combined with the XRD patterns of GO‐TiO 2 , find GO‐TiO 2 materials were successfully prepared 25,26 …”
Section: Resultsmentioning
confidence: 99%
“…Most of the adsorbent materials take only 120–150 min at room temperature for the complete removal of pollutants that offers both a quick and cost-effective alternate among a range of materials and procedures. Considering the high surface area and oxy-functionalities of GO and bandgap reduction quality of composites synthesized by decorating semiconductor NPs such as ZnO, ZnS, WO 3 , and Fe 2 O 3 on its surface, these composite materials have significantly been exploited for the adsorptive as well as photocatalytic removal of contaminants from wastewater. TiO 2 NPs are preferred semiconductor nanostructures to form composites due to their higher chemical stability and nonhazardous nature. Previous studies have reported the adsorption efficiency of only TiO 2 NPs around 12%–15%, which could fairly be enhanced by using GO templates significantly .…”
Section: Recent Research Carried Out In Wastewater Treatment Through ...mentioning
confidence: 99%
“…According to related literatures [9][10][11][12][13][14][15], there are a variety of catalysts in photocatalysis, such as TiO 2 , ZnO, BiVO 4 , ZrO 2 , CdS, C 3 N 4 , and so forth. Among them, BiVO 4 is a widely used photocatalytic material due to its better absorption property for visible light.…”
Section: Introductionmentioning
confidence: 99%